Day‐to‐day variations in daily rest periods between working days and recovery from fatigue among information technology workers: One‐month observational study using a fatigue app. Issue 5 (26th September 2018) - Kubo, Tomohide; Izawa, Shuhei; Tsuchiya, Masao; Ikeda, Hiroki; Miki, Keiichi; Takahashi, Masaya
Abstract : Background: The European Union's Working Time Directive stipulates recovery periods as "Eleven consecutive hour daily rest periods (DRPs) between working days." In Japan, adopting this regulation has been discussed. Objective: To examine the association between weekday DRPs and recovery from fatigue by conducting a one‐month observational study using a fatigue monitoring application (fatigue app) on a smart tablet. Methods: Fifty‐five daytime employees working at an information technology company participated in this study. Visual analogue scales (VAS) regarding fatigue, psychological detachment from work, a psychomotor vigilance task (PVT), and sleep‐wake logs were repeatedly measured using a fatigue app that we developed for this study. Sleep was measured by a wrist actigraph. Results: The average and SD of weekday DRPs was 13.1 ± 2.3 h. However, 54.5% of employees experienced less than the minimum 11‐hour DRP at least once a month. Sleep duration was significantly changed with weekday DRPs, though no significant difference was found in sleep efficiency. Linear mixed effects models showed that sleep duration increased by approximately 15 minutes for each hour of weekday DRPs (β = 0.24, 95% CI; 0.17, 0.32, p <.001). VAS‐measured fatigue and psychological detachment from work significantly improved as DRPs increased (β = −3.4, 95% CI; −4.7, −2.1, p <.001; β = 2.6, 95% CI; 1.2, 4.0, p <.001, respectively). However, PVT performance did not significantly change with weekday DRPs. Conclusions: Ensuring weekday DRPs plays an essential role in protecting the opportunities to sleep, with better recovery from fatigue and stress among information technology workers.